Measuring the Quality of Teacher-Constructed English Test as Final Examination through Item Response Theory - Pahrizal, Novri; Otaya, Lian Gafar (English Education Department, 2025)
This study aimed to examine the psychometric quality of a teacher-constructed English final examination test for Grade X students at Senior High School in Sungai Penuh using the framework of Item Response Theory (IRT). The analysis focused on evaluating model fit, item difficulty, and item discrimination parameters across the 1-Parameter Logistic (1-PL) and 2-Parameter Logistic (2-PL) models. Data was collected from students’ responses to 40 multiple-choice items and analyzed using RStudio. The goodness-of-fit results revealed that the 2-PL model provided a better representation of the data, with 36 items classified as fit and only 3 misfitting, compared to the 1-PL model where 32 items fit and 8 misfits. Furthermore, the difficulty parameter (b) indicated that all items were within the acceptable range (–2 ≤ b ≤ +2), with a tendency toward easy to moderate levels. The discrimination parameter (a) demonstrated that most items possessed satisfactory to high discrimination power, although a small number exhibited lower values. These findings confirm that the teacher-constructed test generally meets psychometric standards of validity and reliability, while also highlighting the need for revision of a few misfitting and low-discrimination items. The study provides both theoretical and practical contributions by emphasizing the importance of applying IRT in school-based assessment practices to ensure fair, accurate, and effective evaluation of students’ learning outcomes.